Unzipped carbon nanotubes assisted 3D printable functionalized chitosan hydrogels for strain sensing applications - Patel, Dinesh K.; Won, So-Yeon; Patil, Tejal V.; Dutta, Sayan Deb; Lim, Ki-Taek; Han, Sung Soo (International journal of biological macromolecules, 2024)
Developing multifunctional hydrogels for wearable strain sensors has received significant attention due to their diverse applications, including human motion detection, personalized healthcare, soft robotics, and human-machine interfaces. However, integrating the required characteristics into one component remains challenging. To overcome these limitations, we synthesized multifunctional hydrogels using carboxymethyl chitosan (CMCS) and unzipped carbon nanotubes (f-CNTs) as strain sensor via a one-pot strategy. The polar groups in CMCS and f-CNTs enhance the properties of the hydrogels through different interactions. The hydrogels show superior printability with a uniformity factor (U) of 0.996 ± 0.049, close to 1. The f-CNTs-assisted hydrogels showed improved storage modulus (8.8 × 105 Pa) than the pure polymer hydrogel. The hydrogels adequately adhered to different surfaces, including human skin, plastic, plastic/glass interfaces, and printed polymers. The hydrogels demonstrated rapid self-healing and good conductivity. The biocompatibility of the hydrogels was assessed using human fibroblast cells. No adverse effects were observed with hydrogels, showing their biocompatibility. Furthermore, hydrogels exhibited antibacterial potential against Escherichia coli. The developed hydrogel exhibited unidirectional motion and complex letter recognition potential with a strain sensitivity of 2.4 at 210 % strain. The developed hydrogels could explore developing wearable electronic devices for detecting human motion. [Display omitted] •3D printable and biocompatible hydrogels of functionalized CS/f-CNTs were prepared.•The composite hydrogels exhibited improved mechanical strength and viscoelasticity.•The composite hydrogels showed increased adhesive strength (118.47 kPa).•Hydrogels exhibited real-time motion-sensing potential.•Hydrogels also showed multidimensional movement recognition ability.